Communal Challenges for Child Education in the Digital Era: A Perspective from Gender and Family Power Relations - Siti Syamsiyatun (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2020)
The paper investigates how the digital technology’ advancement has affected our communal being and what could be done to address these challenges. In doing the research, I employ qualitative research to gather the data by documentation, observation, and interview technique with willing and selected informants. My study finds that excessive usage and inability to control the technology endanger human beings, make them submissive to the technology’ logic, and divide community. Community resilience can be achieved if every family units in the neighbourhood are strong and stable. The spread of the COVID-19 pandemic enhances the widespread use of digital technology in many things, such as the learning process, economic transactions; it has changed the social structure. Despite bringing new opportunities, digital technology also presents significant challenges on issues such as gender relations in the family, patterns of parent-child relationships, and even on community health and cohesion. Digital technology might influence the shift of habitus. Still, parents and educational institutions also have the opportunities to contend the digital technological-based habitus and become the axis for the formation of a new habitus for people to navigate their lives guided by love, compassion, and respect.